If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + 1)(x + 3) = 42 Reorder the terms: (1 + 2x)(x + 3) = 42 Reorder the terms: (1 + 2x)(3 + x) = 42 Multiply (1 + 2x) * (3 + x) (1(3 + x) + 2x * (3 + x)) = 42 ((3 * 1 + x * 1) + 2x * (3 + x)) = 42 ((3 + 1x) + 2x * (3 + x)) = 42 (3 + 1x + (3 * 2x + x * 2x)) = 42 (3 + 1x + (6x + 2x2)) = 42 Combine like terms: 1x + 6x = 7x (3 + 7x + 2x2) = 42 Solving 3 + 7x + 2x2 = 42 Solving for variable 'x'. Reorder the terms: 3 + -42 + 7x + 2x2 = 42 + -42 Combine like terms: 3 + -42 = -39 -39 + 7x + 2x2 = 42 + -42 Combine like terms: 42 + -42 = 0 -39 + 7x + 2x2 = 0 Factor a trinomial. (-13 + -2x)(3 + -1x) = 0Subproblem 1
Set the factor '(-13 + -2x)' equal to zero and attempt to solve: Simplifying -13 + -2x = 0 Solving -13 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '13' to each side of the equation. -13 + 13 + -2x = 0 + 13 Combine like terms: -13 + 13 = 0 0 + -2x = 0 + 13 -2x = 0 + 13 Combine like terms: 0 + 13 = 13 -2x = 13 Divide each side by '-2'. x = -6.5 Simplifying x = -6.5Subproblem 2
Set the factor '(3 + -1x)' equal to zero and attempt to solve: Simplifying 3 + -1x = 0 Solving 3 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1x = 0 + -3 -1x = 0 + -3 Combine like terms: 0 + -3 = -3 -1x = -3 Divide each side by '-1'. x = 3 Simplifying x = 3Solution
x = {-6.5, 3}
| rz^5-6r-z^5+6=0 | | 8.17.8= | | 7=-2a | | -6(x-5)+5=35 | | y=6(25) | | 3(6z+-1)+-3(z+1)=11(z+1) | | -4*7*(-6)*5= | | m^3n-11m^2n^2+28mn^3=0 | | 1=6x | | c^2d^2+11cd+28=0 | | 9-(4n-4)=4-5n | | 8x^5+10x^4=4x^3+5x^2 | | (8.83-.33y)+4y=106 | | 2=x+6 | | 4x+5x-9=3x+x+6 | | 3(x-2)-4(x+1)= | | x=-1/2 | | x=-1/2 | | y^2-4y=4 | | 6y-4=2y+10 | | 3x+39=13x-37 | | 2a^2-12a+18=14 | | a-8=13 | | x^2+20x=9 | | h=25-9t | | 6(x+5)-(4x-5)= | | 9y-5=7+8y | | 240000=80x | | 6-(3x-3)-[2(-4x-1)]=-(-3x+2) | | 4y=15-y | | 9y-5(y-2)=12 | | 2x^3-x^2-3x+1=0 |